High-performance conductive degradable carboxylic butadiene-styrene latex as well as preparation method and application thereof
By developing high-performance conductive and degradable carboxylic styrene butadiene latex, the problem of ordinary gloves not working properly when they touch the touch panel is solved, and the conductive latex gloves with excellent conductivity and comfortable wearing are achieved, expanding the application range of the product.
Patent Information
- Application Number
- CN202411674711.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, ordinary gloves cannot work normally when touching the touch panel, resulting in inconvenience of users when using smartphones or operating electronic devices.
Develop a high-performance conductive degradable carboxy styrene butadiene latex to prepare conductive latex gloves with excellent conductivity and comfortable wearing by modifying the formulation of conductive fillers, deionized water, emulsifiers, initiators, styrene monomers, butadiene monomers, methacrylic acid, thiols and degradable materials.
The stable dispersion of conductive silver powder and bentonite is achieved, the conductive properties of carboxylic styrene butadiene latex is improved, and the application range of the product is expanded by adding degradable materials, which is suitable for the preparation of glue-impregnated gloves.
Smart Images

Figure BDA0005146736720000101 
Figure BDA0005146736720000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of styrene butadiene latex production, and in particular to a high-performance conductive degradable carboxyl styrene butadiene latex and a preparation method and application thereof. Background Art
[0002] Carboxylated styrene butadiene latex is a copolymer produced by emulsion polymerization of butadiene, styrene, a small amount of carboxylic acid and other additives. It is a milky white aqueous dispersion with a bluish purple luster. Carboxylated styrene butadiene latex has the advantages of high adhesion and film strength, good mechanical and chemical stability, good fluidity and storage stability, and large filling volume. It is widely used in papermaking, carpets, textiles, accessories, environmentally friendly latex gloves and other industries.
[0003] With the high functionality and diversification of electronic products or electronic devices, more and more electronic devices are equipped with touch panels. However, when users touch the touch panel with ordinary gloves such as leather gloves, knitted gloves made of fiber fabrics, and knitted gloves knitted with yarn, the touch panel does not work because such gloves are non-conductors. Therefore, it is inconvenient to remove the gloves before using a smartphone or operating an electronic device. Therefore, it is very important to develop a conductive latex with excellent conductive properties, and then obtain conductive latex gloves with excellent conductive properties and comfortable to wear. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a high-performance conductive degradable carboxylated styrene butadiene latex and a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a high-performance conductive degradable carboxylated styrene-butadiene latex, comprising the following raw materials:
[0007] Modified conductive filler, deionized water, emulsifier, initiator, styrene monomer, butadiene monomer, methacrylic acid, mercaptan, biodegradable materials;
[0008] The specific formula includes the following raw materials: 0.5-1 part of modified conductive filler, 35-60 parts of deionized water, 3-10 parts of emulsifier, 0.5-1 part of initiator, 10-30 parts of styrene monomer, 10-30 parts of butadiene monomer, 1-2 parts of methacrylic acid, 0.2-0.5 parts of thiol, and 2-8 parts of degradable material.
[0009] Preferably, the high-performance conductive degradable carboxylated styrene-butadiene latex comprises the following raw materials:
[0010] 0.8 parts of modified conductive filler, 50 parts of deionized water, 6 parts of emulsifier, 0.7 parts of initiator, 20% of styrene monomer, 20 parts of butadiene monomer, 1.5 parts of methacrylic acid, 0.35 parts of thiol, and 6 parts of degradable material.
[0011] Preferably, the modified conductive filler comprises 5-10 parts of conductive silver powder, 2-5 parts of bentonite, and 20-50 parts of conductive enhancer;
[0012] The preparation method of the modified conductive filler comprises the following steps:
[0013] S1, mixing the conductive silver powder and bentonite, then adding the conductive synergist, and then heating to 40-60° C. to react the conductive silver powder and bentonite in the conductive particle dispersion for 20-40 minutes to obtain a conductive particle dispersion;
[0014] S2, subjecting the conductive particle dispersion to ultrasonic treatment for 20-30 minutes, and then performing secondary grinding to obtain a grinding liquid;
[0015] S3, add the grinding liquid into the centrifuge, set the speed to 1000-1500r / min, centrifuge for 8-15min, and then remove the upper liquid to obtain the sediment;
[0016] S4. Add ethanol aqueous solution to the sediment and stir evenly, then add it to a centrifuge, set the speed to 1000-1500r / min, centrifuge for 30-50min, then remove the upper liquid and dry it to obtain a modified conductive filler.
[0017] Preferably, the conductive silver powder is selected from flaky silver powder with an average particle size of 3-5 μm or spherical silver powder with an average particle size of 2-6 μm.
[0018] Preferably, the bentonite is a mixture of sodium-based bentonite and calcium-based bentonite, and the mixing ratio of the sodium-based bentonite to the calcium-based bentonite is 6-10:1.
[0019] Preferably, the conductivity enhancer is a mixture of one or more of oxalic acid, succinic acid, ferrocenylcarboxylic acid, ferrocenylacetic acid, ferrocenyldicarboxylic acid and ferrocenyldiacetic acid.
[0020] Preferably, during the secondary grinding in S2, the material is added to a ball mill at a rotation speed of 200 r / min and ground for 8-10 hours to obtain a grinding liquid with an average particle size of 3-5 μm.
[0021] The present invention also provides a method for preparing a high-performance conductive degradable carboxylated styrene-butadiene latex, comprising the following steps:
[0022] Step 1: Add deionized water, emulsifier, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material into a reaction container under vacuum conditions, and then introduce N2 to replace the air in the reaction container for emulsification;
[0023] Step 2: After heating the reaction container to the reaction temperature, add the initiator and mix evenly, keep the temperature for 2.5-4 hours to polymerize to form latex, and when the conversion rate reaches more than 98%, adjust the pH value of the latex to 7-8;
[0024] Step 3: Then add the modified conductive filler and mix, then perform ultrasonic dispersion, and after the temperature drops to 30-50° C., perform vacuum degassing and pack the material to obtain a high-performance conductive biodegradable carboxylated styrene-butadiene latex.
[0025] Preferably, in step three, the vacuum degree of the vacuum degassing treatment is -0.08 to -0.1 MPa, and the treatment time is 30-60 min.
[0026] The high-performance conductive degradable carboxylated styrene butadiene latex prepared by the present invention and its preparation method and application include: conductive silver powder and bentonite are mixed and then washed with an ethanol aqueous solution, and then centrifuged and dried to remove excess ethanol aqueous solution; when ultrasonic dispersion is performed after adding the latex, the performance of the latex is not affected; since the flowability is improved after the bentonite is added, it is beneficial to the discharge of bubbles, and the distance between the modified conductive filler particles is shortened, thereby improving the electrical and thermal conductivity of the degradable carboxylated styrene butadiene latex.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The invention destroys the oxide film on the surface of the conductive silver powder by an acidic conductive synergist, thereby improving the conductivity of the conductive silver powder. Meanwhile, bentonite absorbs water and swells to become very lubricated. After secondary grinding, the particle size of the bentonite is further reduced, and the lubricity of the conductive silver powder is increased after the conductive silver powder and the bentonite are mixed. Thus, in the ultrasonic dispersion process with carboxyl styrene butadiene latex, the conductive silver powder has better flowability, is stably dispersed in the latex, and improves the conductive performance of the carboxyl styrene butadiene latex. Meanwhile, the added degradable material further expands the application range of the product, and the product can be widely used in the preparation of dipped gloves. DETAILED DESCRIPTION
[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention of this embodiment provides a high-performance conductive degradable carboxylated styrene-butadiene latex, which can be used to prepare dipped gloves, comprising the following raw materials: modified conductive filler, deionized water, emulsifier, initiator, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material;
[0031] The specific formula includes the following raw materials: 0.5-1 part of modified conductive filler, 35-60 parts of deionized water, 3-10 parts of emulsifier, 0.5-1 part of initiator, 10-30 parts of styrene monomer, 10-30 parts of butadiene monomer, 1-2 parts of methacrylic acid, 0.2-0.5 parts of mercaptan, and 2-8 parts of degradable material;
[0032] The degradable material is polycaprolactone or polyvinyl alcohol.
[0033] The high-performance conductive degradable carboxylated styrene-butadiene latex of this embodiment comprises the following raw materials:
[0034] 0.8 parts of modified conductive filler, 50 parts of deionized water, 6 parts of emulsifier, 0.7 parts of initiator, 20% of styrene monomer, 20 parts of butadiene monomer, 1.5 parts of methacrylic acid, 0.35 parts of thiol, and 6 parts of degradable material.
[0035] The modified conductive filler of this embodiment includes 5-10 parts of conductive silver powder, 2-5 parts of bentonite, and 20-50 parts of conductive synergist (by mass);
[0036] The preparation method of the modified conductive filler comprises the following steps:
[0037] S1, mixing the conductive silver powder and bentonite, then adding a conductive synergist, and then heating to 40-60° C., allowing the conductive silver powder and bentonite to react in the conductive particle dispersion for 20-40 minutes to obtain a conductive particle dispersion, and using the acidic conductive synergist to destroy the oxide film on the surface of the conductive silver powder to improve the conductivity of the conductive silver powder;
[0038] S2, subjecting the conductive particle dispersion to ultrasonic treatment for 20-30 minutes, and then performing secondary grinding to obtain a grinding liquid, the secondary grinding makes the bentonite and the conductive silver powder equal in size, and the conductive silver powder and the bentonite are mixed to increase the lubricity of the conductive silver powder;
[0039] S3, add the grinding liquid into the centrifuge, set the speed to 1000-1500r / min, centrifuge for 8-15min, and then remove the upper liquid to obtain the sediment;
[0040] S4. Add ethanol aqueous solution to the sediment and stir evenly, then add it to a centrifuge, set the speed to 1000-1500r / min, centrifuge for 30-50min, then remove the upper liquid and dry it to obtain a modified conductive filler. The ethanol aqueous solution is 60-70%, the drying temperature is 30-40°C, and the drying time is 1-2h. Centrifugation and drying are performed to remove excess ethanol aqueous solution. When ultrasonic dispersion is performed after adding latex, the performance of the latex will not be affected.
[0041] The conductive silver powder of this embodiment is selected from flaky silver powder with an average particle size of 3-5 μm or spherical silver powder with an average particle size of 2-6 μm.
[0042] The bentonite in this embodiment is a mixture of sodium-based bentonite and calcium-based bentonite, and the mixing ratio of the sodium-based bentonite to the calcium-based bentonite is 6-10:1.
[0043] The conductivity enhancer of this embodiment is a mixture of one or more of oxalic acid, succinic acid, ferrocenylcarboxylic acid, ferrocenylacetic acid, ferrocenyldicarboxylic acid, and ferrocenyldiacetic acid.
[0044] During the secondary grinding in S2 of this embodiment, the mixture is put into a ball mill at a rotation speed of 200 r / min and ground for 8-10 hours to obtain a grinding liquid with an average particle size of 3-5 μm.
[0045] A method for preparing a high-performance conductive degradable carboxylated styrene-butadiene latex according to the present embodiment comprises the following steps:
[0046] Step 1: Add deionized water, emulsifier, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material into a reaction container under vacuum conditions, and then introduce N2 to replace the air in the reaction container for emulsification;
[0047] Step 2: After heating the reaction container to the reaction temperature, add the initiator and mix evenly, keep the temperature for 2.5-4 hours to polymerize to form latex, and when the conversion rate reaches more than 98%, adjust the pH value of the latex to 7-8;
[0048] Step 3: Then add the modified conductive filler and mix, then perform ultrasonic dispersion, and after the temperature drops to 30-50° C., perform vacuum degassing and pack the material to obtain a high-performance conductive biodegradable carboxylated styrene-butadiene latex.
[0049] In step three of this embodiment, the vacuum degree of the vacuum degassing treatment is -0.08 to -0.1 MPa, and the treatment time is 30-60 min.
[0050] Example 1.
[0051] The present invention of this embodiment provides a high-performance conductive degradable carboxylated styrene butadiene latex, comprising the following raw materials: modified conductive filler, deionized water, emulsifier, initiator, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material;
[0052] The specific formula includes the following raw materials: 0.5 parts of modified conductive filler, 35 parts of deionized water, 3 parts of emulsifier, 0.5 parts of initiator, 10 parts of styrene monomer, 10 parts of butadiene monomer, 1 part of methacrylic acid, 0.2 parts of thiol, and 2 parts of degradable material.
[0053] The modified conductive filler of this embodiment includes 5 parts of conductive silver powder, 2 parts of bentonite, and 20 parts of conductive enhancer;
[0054] The preparation method of the modified conductive filler comprises the following steps:
[0055] S1, mixing the conductive silver powder and bentonite, then adding the conductive synergist, and then heating to 40° C. to allow the conductive silver powder and bentonite to react in the conductive particle dispersion for 20 min to obtain a conductive particle dispersion;
[0056] S2, subjecting the conductive particle dispersion to ultrasonic treatment for 20 minutes, and then performing secondary grinding to obtain a grinding liquid;
[0057] S3, adding the grinding liquid into the centrifuge, setting the speed to 1000r / min, centrifuging for 8min, and then removing the upper liquid to obtain the sediment;
[0058] S4. Add ethanol aqueous solution to the sediment and stir evenly, then add it to a centrifuge, set the speed to 1000r / min, centrifuge for 30min, then remove the upper liquid and dry it to obtain a modified conductive filler.
[0059] The conductive silver powder of this embodiment is selected from flaky silver powder with an average particle size of 3 μm or spherical silver powder with an average particle size of 2 μm.
[0060] The bentonite in this embodiment is a mixture of sodium-based bentonite and calcium-based bentonite, and the mixing ratio of the sodium-based bentonite to the calcium-based bentonite is 6:1.
[0061] The conductivity enhancer of this embodiment is a mixture of one or more of oxalic acid, succinic acid, ferrocenylcarboxylic acid, ferrocenylacetic acid, ferrocenyldicarboxylic acid, and ferrocenyldiacetic acid.
[0062] During the secondary grinding in S2 of this embodiment, the mixture was put into a ball mill at a rotation speed of 200 r / min and ground for 8 hours to obtain a grinding liquid with an average particle size of 3 μm.
[0063] A method for preparing a high-performance conductive degradable carboxylated styrene-butadiene latex according to the present embodiment comprises the following steps:
[0064] Step 1: Add deionized water, emulsifier, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material into a reaction container under vacuum conditions, and then introduce N2 to replace the air in the reaction container for emulsification;
[0065] Step 2: After heating the reaction container to the reaction temperature, add the initiator and mix evenly, keep the temperature for 2.5 hours to polymerize to form latex, and when the conversion rate reaches more than 98%, adjust the pH value of the latex to 7;
[0066] Step 3: Then add the modified conductive filler and mix, then perform ultrasonic dispersion, and after the temperature drops to 30° C., perform vacuum degassing and pack the material to obtain a high-performance conductive biodegradable carboxylated styrene-butadiene latex.
[0067] In step three of this embodiment, the vacuum degree of the vacuum degassing treatment is -0.08 MPa, and the treatment time is 30 min.
[0068] Example 2.
[0069] The present invention of this embodiment provides a high-performance conductive degradable carboxylated styrene butadiene latex, comprising the following raw materials: modified conductive filler, deionized water, emulsifier, initiator, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material;
[0070] The specific formula includes the following raw materials: 0.8 parts of modified conductive filler, 50 parts of deionized water, 6 parts of emulsifier, 0.7 parts of initiator, 20% of styrene monomer, 20 parts of butadiene monomer, 1.5 parts of methacrylic acid, 0.35 parts of thiol, and 6 parts of degradable material.
[0071] The modified conductive filler of this embodiment includes 8 parts of conductive silver powder, 3 parts of bentonite, and 35 parts of conductive enhancer;
[0072] The preparation method of the modified conductive filler comprises the following steps:
[0073] S1, mixing the conductive silver powder and bentonite, then adding the conductive synergist, and then heating to 50° C. to allow the conductive silver powder and bentonite to react in the conductive particle dispersion for 25 min to obtain a conductive particle dispersion;
[0074] S2, subjecting the conductive particle dispersion to ultrasonic treatment for 25 minutes, and then performing secondary grinding to obtain a grinding liquid;
[0075] S3, adding the grinding liquid into the centrifuge, setting the speed to 1300r / min, centrifuging for 11min, and then removing the upper liquid to obtain the sediment;
[0076] S4. Add ethanol aqueous solution to the sediment and stir evenly, then add it to a centrifuge, set the speed to 1200r / min, centrifuge for 40min, then remove the upper liquid and dry it to obtain a modified conductive filler.
[0077] The conductive silver powder of this embodiment is selected from flaky silver powder with an average particle size of 4 μm or spherical silver powder with an average particle size of 2-6 μm.
[0078] The bentonite in this embodiment is a mixture of sodium-based bentonite and calcium-based bentonite, and the mixing ratio of the sodium-based bentonite to the calcium-based bentonite is 8:1.
[0079] The conductivity enhancer of this embodiment is a mixture of one or more of oxalic acid, succinic acid, ferrocenylcarboxylic acid, ferrocenylacetic acid, ferrocenyldicarboxylic acid, and ferrocenyldiacetic acid.
[0080] During the secondary grinding in S2 of this embodiment, the slurry was added into a ball mill with a rotation speed of 200 r / min and ground for 9 hours to obtain a grinding liquid with an average particle size of 4 μm.
[0081] A method for preparing a high-performance conductive degradable carboxylated styrene-butadiene latex according to the present embodiment comprises the following steps:
[0082] Step 1: Add deionized water, emulsifier, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material into a reaction container under vacuum conditions, and then introduce N2 to replace the air in the reaction container for emulsification;
[0083] Step 2: After heating the reaction container to the reaction temperature, add the initiator and mix evenly, keep the temperature for 3 hours to polymerize to form latex, and when the conversion rate reaches more than 98%, adjust the pH value of the latex to 7.5;
[0084] Step 3: Then add the modified conductive filler and mix, then perform ultrasonic dispersion, and after the temperature drops to 40° C., perform vacuum degassing and pack the material to obtain a high-performance conductive biodegradable carboxylated styrene-butadiene latex.
[0085] In step three of this embodiment, the vacuum degree of the vacuum degassing treatment is -0.09 MPa, and the treatment time is 50 min.
[0086] Example 3.
[0087] The present invention of this embodiment provides a high-performance conductive degradable carboxylated styrene butadiene latex, comprising the following raw materials: modified conductive filler, deionized water, emulsifier, initiator, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material;
[0088] The specific formula includes the following raw materials: 1 part of modified conductive filler, 60 parts of deionized water, 10 parts of emulsifier, 1 part of initiator, 30 parts of styrene monomer, 30 parts of butadiene monomer, 2 parts of methacrylic acid, 0.5 parts of thiol, and 8 parts of degradable material.
[0089] The modified conductive filler of this embodiment includes 10 parts of conductive silver powder, 5 parts of bentonite, and 50 parts of conductive enhancer;
[0090] The preparation method of the modified conductive filler comprises the following steps:
[0091] S1, mixing the conductive silver powder and bentonite, then adding the conductive synergist, and then heating to 60° C. to allow the conductive silver powder and bentonite to react in the conductive particle dispersion for 40 min to obtain a conductive particle dispersion;
[0092] S2, subjecting the conductive particle dispersion to ultrasonic treatment for 30 minutes, and then performing secondary grinding to obtain a grinding liquid;
[0093] S3, adding the grinding liquid into the centrifuge, setting the speed to 1500r / min, centrifuging for 15min, and then removing the upper liquid to obtain the sediment;
[0094] S4. Add ethanol aqueous solution to the sediment and stir evenly, then add it to a centrifuge, set the speed to 1500r / min, centrifuge for 50min, then remove the upper liquid and dry it to obtain a modified conductive filler.
[0095] The conductive silver powder of this embodiment is selected from flaky silver powder with an average particle size of 5 μm or spherical silver powder with an average particle size of 6 μm.
[0096] The bentonite in this embodiment is a mixture of sodium-based bentonite and calcium-based bentonite, and the mixing ratio of the sodium-based bentonite to the calcium-based bentonite is 10:1.
[0097] The conductivity enhancer of this embodiment is a mixture of one or more of oxalic acid, succinic acid, ferrocenylcarboxylic acid, ferrocenylacetic acid, ferrocenyldicarboxylic acid, and ferrocenyldiacetic acid.
[0098] During the secondary grinding in S2 of this embodiment, the mixture was added to a ball mill at a rotation speed of 200 r / min and ground for 10 hours to obtain a grinding liquid with an average particle size of 5 μm.
[0099] A method for preparing a high-performance conductive degradable carboxylated styrene-butadiene latex according to the present embodiment comprises the following steps:
[0100] Step 1: Add deionized water, emulsifier, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material into a reaction container under vacuum conditions, and then introduce N2 to replace the air in the reaction container for emulsification;
[0101] Step 2: After heating the reaction container to the reaction temperature, add the initiator and mix evenly, keep the temperature for 4 hours to polymerize to form latex, and when the conversion rate reaches more than 98%, adjust the pH value of the latex to 8;
[0102] Step 3: Then add the modified conductive filler and mix, then perform ultrasonic dispersion, and after the temperature drops to 50° C., perform vacuum degassing and pack the material to obtain a high-performance conductive biodegradable carboxylated styrene-butadiene latex.
[0103] In step three of this embodiment, the vacuum degree of the vacuum degassing treatment is 0.1 MPa, and the treatment time is 60 min.
[0104] Comparative Example 1.
[0105] The difference from Example 3 is that the carboxylated styrene butadiene latex is prepared using a conventional method.
[0106] Comparative Example 2.
[0107] The difference from Example 3 is that common conductive silver powder is used to prepare carboxylated styrene butadiene latex.
[0108] The products of Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests;
[0109] Five groups of carboxylated styrene butadiene latex samples were prepared, each group corresponding to Examples 1-3 and Comparative Examples 1-2 and numbered A / B / C / D / E. Finally, the carboxylated styrene butadiene latex samples of groups A / B / C / D / E were tested respectively. The test results are shown in the following table.
[0110]
[0111]
[0112] It can be seen from Examples 1-3 that the high-performance conductive degradable carboxylated styrene butadiene latex prepared by the present invention is used, the conductive silver powder is mixed with bentonite, and then washed with an ethanol aqueous solution, and then centrifuged and dried to remove excess ethanol aqueous solution. When ultrasonic dispersion is performed after adding latex, the performance of the latex is not affected. At the same time, the added degradable material further expands the application range of the product, and it can be widely used in the preparation of dipped gloves.
[0113] In addition, Examples 1-3 and Comparative Example 2 found that by destroying the oxide film on the surface of the conductive silver powder, the conductivity was improved, and the fluidity of the conductive silver powder increased after mixing with bentonite, thereby making the fluidity of the conductive silver powder better during the ultrasonic dispersion process with carboxylated styrene butadiene latex, and stably dispersed in the latex, thereby improving the conductive properties of the carboxylated styrene butadiene latex.
[0114] The innovation of the present invention is:
[0115] The invention destroys the oxide film on the surface of the conductive silver powder by an acidic conductive synergist, thereby improving the conductivity of the conductive silver powder. Meanwhile, bentonite absorbs water and swells to become very lubricated. After secondary grinding, the particle size of the bentonite is further reduced, and the lubricity of the conductive silver powder is increased after the conductive silver powder and the bentonite are mixed. Thus, in the ultrasonic dispersion process with carboxyl styrene butadiene latex, the conductive silver powder has better flowability, is stably dispersed in the latex, and improves the conductive performance of the carboxyl styrene butadiene latex. Meanwhile, the added degradable material further expands the application range of the product, and the product can be widely used in the preparation of dipped gloves.
[0116] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0117] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high-performance conductive degradable carboxylated styrene-butadiene latex, characterized in that: The raw materials include: modified conductive filler, deionized water, emulsifier, initiator, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable materials; The specific formula includes the following raw materials (by mass): 0.5-1 part of modified conductive filler, 35-60 parts of deionized water, 3-10 parts of emulsifier, 0.5-1 part of initiator, 10-30 parts of styrene monomer, 10-30 parts of butadiene monomer, 1-2 parts of methacrylic acid, 0.2-0.5 parts of thiol, and 2-8 parts of degradable material.
2. A high-performance conductive degradable carboxylated styrene-butadiene latex according to claim 1, characterized in that: Including the following ingredients: 0.8 parts of modified conductive filler, 50 parts of deionized water, 6 parts of emulsifier, 0.7 parts of initiator, 20% of styrene monomer, 20 parts of butadiene monomer, 1.5 parts of methacrylic acid, 0.35 parts of thiol, and 6 parts of degradable material.
3. The high-performance conductive degradable carboxylated styrene-butadiene latex according to claim 1, characterized in that: The modified conductive filler comprises 5-10 parts of conductive silver powder, 2-5 parts of bentonite, and 20-50 parts of conductive enhancer; The preparation method of the modified conductive filler comprises the following steps: S1, mixing the conductive silver powder and bentonite, then adding the conductive synergist, and then heating to 40-60° C. to allow the conductive silver powder and bentonite to react in the conductive particle dispersion for 20-40 minutes to obtain a conductive particle dispersion; S2, subjecting the conductive particle dispersion to ultrasonic treatment for 20-30 minutes, and then performing secondary grinding to obtain a grinding liquid; S3, add the grinding liquid into the centrifuge, set the speed to 1000-1500r / min, centrifuge for 8-15min, and then remove the upper liquid to obtain the sediment; S4. Add ethanol aqueous solution to the sediment and stir evenly, then add it to a centrifuge, set the speed to 1000-1500r / min, centrifuge for 30-50min, then remove the upper liquid and dry it to obtain a modified conductive filler.
4. A high-performance conductive degradable carboxylated styrene-butadiene latex according to claim 3, characterized in that: The conductive silver powder is selected from flaky silver powder with an average particle size of 3-5 μm or spherical silver powder with an average particle size of 2-6 μm.
5. The high-performance conductive degradable carboxylated styrene-butadiene latex according to claim 3, characterized in that: The bentonite is a mixture of sodium-based bentonite and calcium-based bentonite, and the mixing ratio of the sodium-based bentonite and the calcium-based bentonite is 6-10:
1.
6. The high-performance conductive degradable carboxylated styrene-butadiene latex according to claim 3, characterized in that: The conductive enhancer is a mixture of one or more of oxalic acid, succinic acid, ferrocenylcarboxylic acid, ferrocenylacetic acid, ferrocenyldicarboxylic acid and ferrocenyldiacetic acid.
7. The high-performance conductive degradable carboxylated styrene-butadiene latex according to claim 3, characterized in that: During the secondary grinding in S2, the mixture is put into a ball mill at a rotation speed of 200 r / min and ground for 8-10 hours to obtain a grinding liquid with an average particle size of 3-5 μm.
8. A method for preparing a high-performance conductive degradable carboxylated styrene-butadiene latex according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Add deionized water, emulsifier, styrene monomer, butadiene monomer, methacrylic acid, thiol, and degradable material into a reaction container under vacuum conditions, and then introduce N2 to replace the air in the reaction container for emulsification; Step 2: After heating the reaction container to the reaction temperature, add the initiator and mix evenly, keep the temperature for 2.5-4 hours to polymerize to form latex, and when the conversion rate reaches more than 98%, adjust the pH value of the latex to 7-8; Step 3: Then add the modified conductive filler and mix, then perform ultrasonic dispersion, and after the temperature drops to 30-50° C., perform vacuum degassing and pack the material to obtain a high-performance conductive biodegradable carboxyl styrene butadiene latex.
9. The method for preparing a high-performance conductive degradable carboxylated styrene-butadiene latex according to claim 8, characterized in that: In the step 3, the vacuum degree of the vacuum degassing treatment is -0.08 to -0.1 MPa, and the treatment time is 30-60 min.
10. Use of the high-performance conductive degradable carboxylated styrene-butadiene latex according to any one of claims 1 to 9 in the preparation of dipped gloves.